2016
DOI: 10.1089/lgbt.2015.0090
|View full text |Cite
|
Sign up to set email alerts
|

The Health Effects of Masculine Self-Esteem Following Treatment for Localized Prostate Cancer Among Gay Men

Abstract: Purpose: To identify factors associated with masculine self-esteem in gay men following treatment for localized prostate cancer (PCa) and to determine the association between masculine self-esteem, PCa-specific factors, and mental health factors in these patients. Methods: A national cross-sectional survey of gay PCa survivors was conducted in 2010-2011. To be eligible for the study, men needed to be age 50 or older, reside in the United States, self-identify as gay, able to read, write, and speak English, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…Five articles (Allensworth‐Davies et al, ; Crangle, Latini, & Hart, ; Thomas et al, ; Ussher et al, ; Ussher, Rose et al, ) reported that prostate cancer treatment had a resounding impact on GBQ men's mental and emotional health, with treatment being directly correlated with increased symptoms of anxiety and depression. Other men reported feeling grief and regret.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five articles (Allensworth‐Davies et al, ; Crangle, Latini, & Hart, ; Thomas et al, ; Ussher et al, ; Ussher, Rose et al, ) reported that prostate cancer treatment had a resounding impact on GBQ men's mental and emotional health, with treatment being directly correlated with increased symptoms of anxiety and depression. Other men reported feeling grief and regret.…”
Section: Resultsmentioning
confidence: 99%
“…One man said that, after treatment, he was “still kind of getting out of this, but for a long time I felt like I was severely damaged; [and] therefore, completely undesirable. I withdrew (Rosser et al, ).” Another said that prostate cancer treatment was like going through “menopause in a male body” (Allensworth‐Davies et al, ; Rosser et al, ; Thomas et al, ; Ussher et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…It is important that patients with prostate cancer can discuss sexual concerns in supportive environment with health professionals. A cross‐sectional survey study in the USA showed that men who reported feeling comfortable revealing their sexual orientation to their doctor reported higher masculine self‐esteem scores than men who did not (Allensworth‐Davies et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The doctoral dissertation compared 341 heterosexual men with 111 gay men, finding GBM to report lower masculine self-esteem and less partner affection than heterosexual men with prostate cancer(Allensworth-Davies, 2012). The author posits that greater sensitivity to stigma as a sexual minority could result in poorer overall quality of life compared to heterosexual men.…”
Section: Introductionmentioning
confidence: 99%